Strategi Pemasaran Industri Tahu Pada Masa Pandemi Covid-19 (Studi Pada Omah Tahu Asri Serasi Bandungan) - Rossitasari, Rossitasari; Maria, Maria (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 10 No 1 (2022): Jurnal Manajemen AgribisnisDO - 10.24843/JMA.2022.v10.i01.p03, 2022)
The impact of Covid-19 has made market demand unstable, thereby reducing the income and production of Omah Tahu Asri Serasi. The Policy of imposing restrictions on community activities and the relocation of the new Bandungan products during the Covid-19 pandemic and identify internal and external factors (strenghts and wekanesses as well as opportunities and threats) in the marketing strategi at Omah Tahu Asri Serasi Bandungan during the Covid-19 pandemic. Research at Omah Tahu Asri Serasi Bandungan. This type of research is qualitative, the technique of determining key informants and informants uses purposive. The method of analysisi using SWOT. The resultas of the study show that internal factors are the main strenghts, namely cooperation with traders and developing strategies, the main weakness is a decrease in income and has not promoted effectively. The external factor that became the main opportuity was the popularity of Tahu Asri Serasi and traders helping to expand the market. The main threat is the uncertain purchasing power of consumers due to the pandemic and the prices of other Tofu Serasi are lower than other tofu products. The SWOT analysis quadrant, Omah Tahu Asri Serasi shoes quadrant Im using a progressive strategy. The condition of ofu demand continues to increase, so it is very possible to expand, enlarge growth and achieve maximum progress durig the Covid-19 pandemic.